Living ideas, T&T Home Improvement Centre: Terminal year end report - Balolong, Grace (Animo Repository, 2021)
The research paper explores the challenges and learnings that the proponents faced whilst conducting their family business internship under a pandemic. Three full terms with two different family businesses, the paper will be showcasing the group's difficulties and successes per business and how they were able to overcome their mistakes. A long journey of endless working and learning, this paper will discuss the group's progress, achievements, obstacles and major learnings that they will be applying in the future as they put one step forward into graduation.